اﻟﺗﻌﻠق اﻟﺗﺟﻧﺑﻲ وﻋﻼﻗﺗﮫ ﺑﺎﻟﺛﻘﺔ ﺑﺎﻟﻧﻔس ﻟدى أطﻔﺎل اﻟرﯾﺎض (Journal of the College of Education for Women, 2019)
The problem with search in multiple positions that shows where kids behavior Talaa resulting in an imbalance in the balance of the child's personality and future results on his being psychological and that stand in front of achieving individual to itself and to confirm his self-confidence so many of the parents overlook behaviors their children have Aergon to reasons The real behind it, including the form of attachment shown by children to their parents and their reaction towards him and for that researchers resorted to Search attachment Altjunba and its relationship to self-esteem. The research aims verification of goals: 1- dangling the Altjunba the children Riyadh. 2- significant differences between males and females and kindergarten and preschool variable depending on dangling Altjunba. And on the foregoing we can put the following assumptions: A- There are significant differences between males and females. - There are significant differences between the kindergarten and preschool children in dangling Altjunba variable. ١٦٦3- self-confidence in children. 4- Relationship between attachment Altjunba and self-confidence. Sample: Sample Stability 40 or mothers of children Riyadh. Sample discrimination 250 or mothers of children Riyadh. Sample application 250 or mothers of children Riyadh. Adata: The researchers collect answers and arrange paragraphs scale n (35) paragraph of the comment Altjunba and put alternatives apply to him always, sometimes, does not apply and never measure self-esteem consists of (26) paragraph and put alternatives apply to him (always, sometimes, does not apply at all). The researchers distributed questionnaires to the experts and found that divides truth and a plant that is () Then correct scores (3-2-1) and was the highest score (105) and a lower (35) was applied to a sample of (40) or mothers of Riyadh. The findings researchers are: 1- a measure of the attached the Altjunba the children Riyadh. 2 - There are significant differences between males and females in dangling Altjunba variable. 3 - There are significant differences between the kindergarten and preschool children in dangling Altjunba variable. 4- measure the self-confidence of children Riyadh. 5 - Know the relationship between attachment Altjunba and self-confidence of children Riyadh.